An investigation to determine if the theatre time allocated to the obstetric theatre at Pelonomi Hospital is being utilised appropriately - Swart, Matthys Lourens (University of the Free State, 2021)
Background. Operating theatre efficiency is a priority from both a financial and patient care perspective. Optimal theatre efficiency is required to prevent prolonged waiting time for surgery, which can lead to deterioration of a patient's health, prolonged hospitalisation, anxiety, inconvenience, staff frustration and increased costs. Objectives. The aim of this study was to determine if theatre time was being used efficiently in the obstetric theatre at Pelonomi Tertiary Hospital, Bloemfontein, by investigating the amount of time the theatre was not in use during working hours and after hours, and to determine whether when an elective case was done after hours, if there was time available during working hours when it could have been done. Methods. The study design involved a retrospective investigation. The obstetric theatre register was used to collect the data. The data collected from this register included the type of surgery, start and end times of the operation, and whether it was an emergency or elective procedure. Results. The study period was 01/07/2019 and 31/12/2019. In total, 1 048 caesarean sections were performed; 1 020 (97.3%) were emergency cases. Of the 28 elective cases, nine (32.1%) were done after hours. The amount of time the theatre was not in use during working hours ranged from a minimum of 1 hour and 35 minutes (1h 35m) to a maximum of 8h 40m, with a median of 5h 20m. The median theatre utilisation during working hours was 44%. The amount of time the theatre was not in use after hours on a week day ranged from a minimum of 45 minutes to a maximum of 12h 15m, with a median of 7h 40m, which was equal to median theatre utilisation of 47%. The median amount of time the theatre was not in use on public holidays and weekends combined was 10h 25m per 24-hour day (range 1h 15m to 17h 40m), which was equal to median theatre utilisation of 57%. First case start times (FCSTs) on normal work days, after 7h30, were a median of 2 hours, ranging from 5 minutes to 8h 40m. Conclusions. This study showed inefficient use of obstetric theatre time, at Pelonomi Tertiary Hospital, as some elective C-sections were done after hours when enough time were available during working hours. Remarkably few cases were classified as elective cases and needs further investigation. The possibility exists of calling most cases an emergency to justify doing it after hours.
Dissertation (M.Med (Anaesthesiology))--University of the Free State, 2021
Keywords: Operating theatre efficiency; Theatre utilisation; First case start time; Obstetric; Caesarean section; Emergency; Elective